ENT 600 : Tennis wall performance / Ahmad Ridzuan Midan … [et al.] - Midan, Ahmad Ridzuan; Abd Hamid, Khairul Azmie; Mohamed Safuan, Mawardi; Mohd Basri, Mohammad Azli; Jamaludin, Mohamad Firdaus (2015)
The product that will be developed by the team is going to help the tennis player to improve and to guide the player during practice. Before this they do not know how their level of performance if just they are playing with the null wall or opponent. Either their technique is improving or not it is not certain to tell. So "Tennis Wall Performance" that will be developed to overcome this issue. With this product the tennis player can help to improve their performance during practice without a coach in attendance.